A GUIDED SWAT MODEL APPLICATION ON SEDIMENT YIELD MODELING IN PANGANI RIVER BASIN: LESSONS LEARNT - Preksedis Marco Ndomba; Felix W. Mtalo; Ånund Killingtveit (Journal of Urban and Environmental Engineering, 2008)
The overall objective of this paper is to report on the lessons learnt from applying Soil and Water Assessment Tool (SWAT) in a well guided sediment yield modelling study. The study area is the upstream of Pangani River Basin (PRB), the Nyumba Ya Mungu (NYM) reservoir catchment, located in the North Eastern part of Tanzania. It should be noted that, previous modeling exercises in the region applied SWAT with preassumption that inter-rill or sheet erosion was the dominant erosion type. In contrast, in this study SWAT model application was guided by results of analysis of high temporal resolution of sediment flow data and hydro-meteorological data. The runoff component of the SWAT model was calibrated from six-years (i.e. 1977–1982) of historical daily streamflow data. The sediment component of the model was calibrated using one-year (1977–1988) daily sediment loads estimated from one hydrological year sampling programme (between March and November, 2005) rating curve. A long-term period over 37 years (i.e. 1969–2005) simulation results of the SWAT model was validated to downstream NYM reservoir sediment accumulation information. The SWAT model captured 56 percent of the variance (CE) and underestimated the observed daily sediment loads by 0.9 percent according to Total Mass Control (TMC) performance indices during a normal wet hydrological year, i.e., between November 1, 1977 and October 31, 1978, as the calibration period. SWAT model predicted satisfactorily the long-term sediment catchment yield with a relative error of 2.6 percent. Also, the model has identified erosion sources spatially and has replicated some erosion processes as determined in other studies and field observations in the PRB. This result suggests that for catchments where sheet erosion is dominant SWAT model may substitute the sediment-rating curve. However, the SWAT model could not capture the dynamics of sediment load delivery in some seasons to the catchment outlet.